Study of dielectric-loaded waveguide slot antennas - Zheng, Boyu (2008)
Waveguide slot antenna has found wide applications in modern communication systems due to its attractive features such as low loss, high efficiency and high power handling capacity. Loading dielectric materials in the conventional air-filled waveguide can reduce its size and weight as well as shorten the guided wavelength. In this thesis, a hybrid mode-matching/moment technique has been developed for analyzing both transverse and longitudinal slots cut on the broad wall of a rectangular waveguide partially loaded with an H-plane dielectric slab. The accuracy and efficiency of our full-wave method has been demonstrated. The radiation patterns of the dielectric-loaded waveguide slot antennas have been investigated by the combination of the proposed hybrid method and the Geometrical Theory of Diffraction. The mutual coupling between rectangular slots cut on a partially dielectric-loaded rectangular waveguide has also been examined. An 8-element nonuniform slot array has been designed, fabricated and tested. It has been observed that the main-to-side lobe ratio is better than 15 dB in the frequency range of 1 GHz. The advantage of using nonuniform spacing for waveguide slot arrays has been illustrated.